Value of Gene Polymorphism in the Development of Allergic Disease in Children - T.E. Shumna; S.V. Soloviova; T.P. Zinchenko; V.I. Mazur (Zaslavsky O.Yu., 2016)
The present literature review has allowed familiarize with a perspective direction of modern medicine, namely DNA researches of polymorphic genes. Determining of genes structure coding albuminous molecules, as well as introduction of new diagnostic technologies in a routine laboratory practice have made possible testing various gene polymorphisms, that allows predict risks of progress of certain diseases in an individual. In particular, genetic testing allows reveal hereditary predisposition to progression of an allergic pathology, namely bronchial asthma, an allergic rhinitis or atopic dermatitis.